Factors related to the occurrence of breast engorgement during the puerperium at the Jawa Maraja Community Health Center - Yessy Arisman; Maulina Mawaddah; Rismaida Saragih; Santika Pebriyanti Ambarita (Institute of Accounting Research and Novation (IARN), 2026)
Background: Breastfeeding is an unbeatable way of providing the ideal nourishment for the healthy growth and development of a baby. Breastfeeding is not always able to run normally, not a few mothers complain of swelling of the breasts, hardness, pain and heat caused by breast milk dams. At the time the researchers conducted the initial survey of 20 postpartum mothers, there were 7 people who experienced breast milk dams. Objective: Factors associated with breast milk retention include family support, frequency of breastfeeding, breast care, breastfeeding position and parity. The research objective was to determine the factors associated with breast milk dams during the postpartum period at the jawa maraja community Health Center. Research Methods: The design of this study used an analytic survey with a cross sectional approach. The population as many as 30 postpartum mothers on day 3 to day 40. The sample in this study was taken using accidental sampling, namely the technique of determining the sample based on chance. Data analysis used univariate and bivariate analysis using the chi-square statistical test. Research Results: The results of the study were based on poor family support as many as 20 respondents (66.7%), 17 respondents (56.7%) had poor breastfeeding frequency (56.7%), 18 respondents (60.0%) had poor breastfeeding, and 18 respondents (60.0%) had poor breastfeeding position. 15 respondents (50.0%), and 18 respondents (60.0%) primiparous parity, 16 respondents (53.3%) had breastfeeding dams with the results of the chi-square test on the family support variable (p value = .0001), breastfeeding frequency (p value = .0001), breast care (p value = .0000), breastfeeding position (p value = .0001) and parity (p value = .0004). Conclusion: The conclusion of this study shows that there is a relationship between family support, breastfeeding frequency, breast care, breastfeeding position and parity with breast milk dams during the postpartum period at the jawa maraja community Health Center . It is recommended that research sites find out about the correct breastfeeding position and the frequency of breastfeeding optimal in order to avoid dam ASI.